2010
DOI: 10.1126/science.1188454
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Microbial Colonization of Germ-Free Mice Reveals the Dynamics of IgA Immune Responses

Abstract: The lower intestine of adult mammals is densely colonized with non-pathogenic (commensal) microbes. Gut bacteria induce protective immune responses, which ensure host-microbial mutualism. The continuous presence of commensal intestinal bacteria has made it difficult to study mucosal immune dynamics. Here we report a reversible germ-free colonization system in mice that is independent of diet or antibiotic manipulation. A slow (>14 days) onset of a long-lived (t1/2>16 weeks), highly specific anti-commensal IgA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
653
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 708 publications
(675 citation statements)
references
References 24 publications
17
653
1
4
Order By: Relevance
“…[81] When the microbiota is depleted (either in GF or antibiotic-treated animals), the immune response is profoundly altered. [7,81] At least some of these immune irregularities in GF mice can be restored by colonization with a normal microbiota [82] or with specific probiotic strains. [83] Additionally, some probiotics have been shown to attenuate pro-inflammatory profiles in cases of pathogen exposure or clinical disease states.…”
Section: Immune Modulation Is a Key Communication Pathway In The Micrmentioning
confidence: 99%
“…[81] When the microbiota is depleted (either in GF or antibiotic-treated animals), the immune response is profoundly altered. [7,81] At least some of these immune irregularities in GF mice can be restored by colonization with a normal microbiota [82] or with specific probiotic strains. [83] Additionally, some probiotics have been shown to attenuate pro-inflammatory profiles in cases of pathogen exposure or clinical disease states.…”
Section: Immune Modulation Is a Key Communication Pathway In The Micrmentioning
confidence: 99%
“…It was reported recently that the maintenance of intestinal IgA production is significantly different from that of systemic IgG production (8). It was found that, in a germ-free condition, antigenspecific IgA + plasma cells could be maintained in the intestine for a long time in the absence of antigenic stimulation (half-life > 16 wk), suggesting that unique intrinsic properties of the IgAproducing plasma cells and intestinal environments might collaborate to maintain the prolonged IgA production.…”
mentioning
confidence: 93%
“…Such approaches hold tremendous promise for unraveling the contributions of both host and microbiota genetics for coadaptation . Hapfelmeier et al (2010) developed a system of ''reversible colonization'' by developing a triple mutant strain of Escherichia coli K12 with three auxotrophic deletions. When fed to gnotobiotic mice, these live but nonreplicating bacteria resulted in mice that were transiently colonized and, as such, provided a system to probe questions of immunological memory regarding antibacterial IgA production in the gut (Hapfelmeier et al 2010).…”
Section: Engineered Microbiomes In Micementioning
confidence: 99%
“…Hapfelmeier et al (2010) developed a system of ''reversible colonization'' by developing a triple mutant strain of Escherichia coli K12 with three auxotrophic deletions. When fed to gnotobiotic mice, these live but nonreplicating bacteria resulted in mice that were transiently colonized and, as such, provided a system to probe questions of immunological memory regarding antibacterial IgA production in the gut (Hapfelmeier et al 2010). As a result of the facile nature of bacterial genetics, rapidly evolving meta'omics technology, and the surge of interest in gnotobiotics, continued technical ingenuity in highly simplified microbial community mouse model systems should be expected.…”
Section: Engineered Microbiomes In Micementioning
confidence: 99%